Development of a novel wear-resistant WC-reinforced coating based on the case-hardening steel Bainidur AM for the substitution of carburizing heat treatments - Bartels, Dominic; Fallqvist, Mikael; Heise, Miriam; Vetter, Johannes; Schmidt, Michael; Krakhmalev, Pavel (Journal of Materials Research and Technology, 2023)
Laser-based directed energy deposition of metals (DED-LB/M) supports the synthesis of functional materials with tailored properties and performance through in-situ modification of the alloying composition within the processing zone. In this investigation, a low-alloyed steel was modified stepwise to analyse the influence of carbon and tungsten carbide (WC) addition on the resulting material properties. A moderate carbon concentration of 0.4 wt.-% improved the average hardness (520 HV0.5). WC particles on the other hand were dissolved within the matrix and resulted in a fine microstructure with high hardness (780 HV0.5). A combined addition of carbon and WC led to the highest material hardness (840 HV0.5). Scratch tests showed that the wear resistance rises with increasing hardness but is improved the most by the addition of hard particles. Furthermore, these tests revealed an anisotropic abrasive wear resistance which correlates with the direction of the weld tracks. Loading the material parallel to the weld track direction led to a homogeneous wear. When the material is scratched perpendicularly to the weld tracks, an inhomogeneous wear with periodic characteristics occurred. The periodicity can be explained by the different microstructural characteristics and hardness at the transition zone between adjacent weld tracks deposited in DED-LB/M. For all materials, the transition between two weld tracks was characterized by a columnar microstructure with low microhardness while the adjacent weld tracks possessed a finer microstructure and higher microhardness. These microstructural differences were mirrored in scratch testing since wear peaks can be observed at the transition zone between two weld tracks.<br
Keywords: DED-LB/M; Wear resistance; Coating; Bainidur AM; Case-hardening steel; Additive manufacturing